ON 2,3-HYPERIDENTITIES IN INVERTIBLE 2,3-ALGEBRAS WITH A BINARY GROUP OPERATION - Ghumashyan, H. E. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
In the present paper the invertible 2,3-algebras with a binary group operation and with balanced first sort 2,3-hyperidentities having length 4 are characterized.